STUDI PEMISAHAN KATION-KATION DENGAN RESIN PENUKAR ANION DAN DENGAN RESIN PENUKAR KATION DALAM MEDIUM TIOSULFAT - Alimin
This research is intended to investigate the possibility of using thiosulphate anion (5 20 3 2-) to separate a binary mixture of Ni(II) and Zn(II) cations using a strongly basic anion exchange resin (Dowex 1 X8; 20-50 mesh, Cl - form) and to separate a binary mixture of Cd(II) and Zn(II) cations using a strongly acidic cation exchange resin (Dowex 50W X8; 100-200 mesh, Na+ form). By determining the distribution coefficients (D) of the L Ni(520 3) 2 complex and of the na(S20 3) 2J2- complex in the anion exchange resin and the distribution coefficients (D) of the Cd(II) cation and of the Zn(II) cation in the cation exchange resin at various concentration of sodium thiosulphate solution, the concentration of sodium thiosuiphate solution giving the maximum value of the separation factorC< (OC=DL (5203 ) 2,2-/D `Ni(S Z03) 2J2- andpC=D Zn(II)/DCd(II) ) can be found. For the separation of the mixture of Ni(II) and Zn(II) cations, using an anion exchange resin, the concentration of sodium thiosulphate solution giving the maximum value of the separation factor (0e= O~ax) was found to be 0.08 M. A statisfactory separation of the chromatographic peaks of the two cations from their mixture was obtained by eluting the Ni(II) cation with 0.08 M sodium thiosuiphate solution and by eluting the Zn(II) cation with a mixture of 10 % sodium chloride solution and ammonia solution (4:l,v/v).For a mixture of Ni(II) and Zn(II) at the weight proportion of 1 : 2 (mg) it was found that the separation gave percent recoveryof 100 % for Ni(II) and for Zn(II). While for mixtures of Ni(II) and Zn(li) in wich the weight proportions are 1 : 1, 1 : 3, 2 : 1, and 3 : 1 (mg) the percent recovery of I1i(II) varies between of 90 % and 105 % and between 100 % and 110% for Zn(II). For the separation of the mixture of Cd(II) and Zn(II) cations, using a cation exchange resin, it was found that a concentration of 0.10 M of sodium thiosulphate solution gave a maximum value of the separation factor ( 0< =Â° max ) Â• A statisfactory separation of the chromatographic peaks of the two cations from their mixture was obtained by eluting Cd(II) cation with 0.10 M sodium thiosulphate solution and by eluting Zn(II) cation with 1.00 M sodium thiosulphate solution..For the mixture of Cd(II) and Zn(II) at a weight proportion of 1 : 1 (mg) it was found that the separation gave a percent recovery of 100 % for Cd(II) and 109 % for Zn(II)